A brain slice experimental model to study the generation and the propagation of focally-induced epileptiform activity - Losi, Gabriele (J Neurosci Methods, 2016)
The early cellular events that in a brain network lead to seizure generation and govern seizure propagation are probably based on different cellular mechanisms. Experimental models in which these events can be separately studied would contribute to improve our understanding of epilepsy. We recently described an in vitro model in entorhinal cortex slices from young rats in which focal seizure-like discharges (SLDs) can be induced in spatially defined regions and at predictable times by local NMDA applications performed in the presence of 4-amimopyridine (4-AP) and low extracellular Mg(2+). Through the use of single-dual cell patch-clamp and field potential recordings, and Ca(2+) imaging from large ensembles of neurons, interneurons and astrocytes, we here extend this model to entorhinal and temporal cortex slices of rat and mouse brain, providing evidence that multiple SLDs exhibiting the typical tonic–clonic discharge pattern can be also evoked in these cortical regions by successive NMDA applications. Importantly, the temporal cortex is more accessible to viral vector injections than the entorhinal cortex: this makes it feasible in the former region the selective expression in inhibitory interneurons or principal neurons of genetically encoded Ca(2+) indicators (GECI) or light-gated opsins. In this model, an optogenetic approach allows to activate specific neuronal types at spatially defined locations, i.e., the focus or the propagating region, and at precise time, i.e., before or during SLD. The NMDA/4-AP model can, therefore, represent a valuable tool to gain insights into the role of specific cell populations in seizure generation, propagation and cessation.